2012
DOI: 10.5664/jcsm.1920
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Sleep Quality of Patients in Intensive Care Unit

Abstract: Introduction: Sleep disturbance is a frequently overlooked complication of intensive care unit (ICU) stay. Aim: To evaluate sleep quality among patients admitted to ICU and investigate environmental and non-environmental factors that affect sleep quality in ICU. Methods: Over a 22-month period, we consecutively recruited patients who spent ≥ 2 nights post-endotracheal extubation in ICU and who were orientated to time, place, and person on the day of discharge. Self-reported sleep quality, according to a modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
120
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(167 citation statements)
references
References 26 publications
(38 reference statements)
12
120
1
7
Order By: Relevance
“…42 The combination of ICU patient care routines (eg, frequent laboratory tests, invasive procedures, fully supportive care), the ICU environment (eg, equipment, alarms, light), and frequent visitation (providers and family) contributes in many ways to sleep disruption for ICU patients. [43][44][45][46][47] Regardless of the cause of sleep disruption, the consequences of lack of sleep include worsening symptoms, physical and cognitive dysfunction, mood instability, and fatigue. 42,43,45,46 This situation raises the question: Why are we, as critical care nurses, disrupting the sleep of patients who are at most risk for complications related to lack of sleep?…”
Section: Promoting Sleep In the Icumentioning
confidence: 99%
See 1 more Smart Citation
“…42 The combination of ICU patient care routines (eg, frequent laboratory tests, invasive procedures, fully supportive care), the ICU environment (eg, equipment, alarms, light), and frequent visitation (providers and family) contributes in many ways to sleep disruption for ICU patients. [43][44][45][46][47] Regardless of the cause of sleep disruption, the consequences of lack of sleep include worsening symptoms, physical and cognitive dysfunction, mood instability, and fatigue. 42,43,45,46 This situation raises the question: Why are we, as critical care nurses, disrupting the sleep of patients who are at most risk for complications related to lack of sleep?…”
Section: Promoting Sleep In the Icumentioning
confidence: 99%
“…[43][44][45][46][47] Regardless of the cause of sleep disruption, the consequences of lack of sleep include worsening symptoms, physical and cognitive dysfunction, mood instability, and fatigue. 42,43,45,46 This situation raises the question: Why are we, as critical care nurses, disrupting the sleep of patients who are at most risk for complications related to lack of sleep? As much as possible, nurses need to restructure their work flow and environment to maximize sleep of critically ill patients.…”
Section: Promoting Sleep In the Icumentioning
confidence: 99%
“…Kortikosteroidlerin, özellikle yüksek dozlarda, yavaş uyku ve REM sürelerini azalttığı bilinmektedir. Antibiyotiklerden bazılarının, özellikle beta-laktam ve kinolonların uyku bozuklukları ile ilişkili olduğu bildirilmiştir (43).…”
Section: İlaçlar Ve Uykuunclassified
“…3,4 Poor sleep quality can be attributed to a variety of environmental factors, which include temperature, light, noise, and mattress quality. 5,6 Addison et al 7 reported that 7% of sleep problems were due to uncomfortable mattresses, which affect the loading of the spine during sleep. 4 Several previous studies have suggested that mattress material can affect sleep quality.…”
Section: Introductionmentioning
confidence: 99%